RISK ASSESSMENT OF HEAVY METAL IN SELECTED SPICES OF LAHORE (The Research of Medical Science Review, 2024)
In this paper, we seek to assess the interelemental concentrations of lead (Pb) and cadmium (Cd) in three popular spices: turmeric powder, black pepper, and white pepper, purchased from various grocery stores in Lahore, Pakistan. Atomic Absorption Spectrophotometry was used to determine the heavy metal concentrations of 18 spice samples that were purchased from six different sources. All samples had cadmium amounts below the WHO safety guideline of 0.3 mg/kg. However, 66.7% of the turmeric and black pepper samples and 83.3% of the white pepper samples had lead levels above the allowable limit of 10 mg/kg. EDI of these metals was also determined for different age and sex classes, which shows that the larger exposure is associated with the higher age, especially for women over 24 years. The Total Hazard Quotient (THQ) and Total Target Hazard Quotient (TTHQ) models were used to assess health hazards. Although turmeric was found to be the primary source of heavy metal exposure, the TTHQ for all age groups was less than 1, indicating generally little cumulative risk. The findings also support the Cookbook Theory by further emphasizing that risks of heavy metal contamination in spices should be constantly monitored and highly regulated. The public should exercise better health premised on better public awareness and measures of quality control recommended to prevent more detrimental effects on consumers.